Heart Rate Response, Temporal Structure and the Stroke Technique Distribution in Table Tennis National Category Matches - Picabea, J. M.; Cámara, J.; Yanci, J. (International Journal of Environmental Research and Public Health, 2022)
The aims of this study were to analyze the heart rate response, the game temporal structure (i.e., mean total time of the matches, real playing time, total rest time) and the stroke technique distribution and to describe its relations in the table tennis national category in simulated competitions. A cohort of 60 table tennis male players (22.06 ± 8.32 years) played 30 simulated matches. The obtained results show a mean heart rate (HRmean) of 142.69 ± 14.10 bpm and a peak heart rate (HRpeak) of 167.26 ± 16.51 bpm. Total strokes were 7505, being the 57.88% and 42.12% forehand and backhand strokes, respectively. The most frequent forehand strokes were service (SERV) (33.13%) and forward spin technique (SPIN) (40.75%) stroke types, with the left quadrant of the table away from the net (Z_5) (25%) and right quadrant of the table away from the net (Z_6) (20.72%) being the most frequent ball bouncing placements. Meanwhile, the most frequent backhand strokes were backspin technique (PUSH) (42.74%) and SPIN (31.86%) stroke types, with the intermediate left quadrant of the table (Z_3) (17.21%), Z_5 (31.22%) and Z_6 (18.54%) being the most frequent ball placements. The mean total time of the matches was 15.74 ± 3.82 min, the mean real playing time was 4.14 ± 1.47 min and the total rest time was 11.60 ± 2.67 min. Heart rate variables did not correlate significantly with the different stroke types or the game temporal variables (p > 0.05). However, stroke types and game temporal structure variables were significantly correlated (p < 0.01). This information can be useful to reveal players` strengths and weaknesses and prepare subsequent training sessions, adapting training sessions to the needs of the athletes.